Influence of bio-inoculants and inorganic fertilizers on yield, nutrient balance,microbial dynamics and quality of strawberry (Fragariax ananassa) under rainfed conditions of Kashmir valley - SINGH, S R; ZARGAR, M Y; SINGH, UMMED; ISHAQ, M (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was conducted during 2006–08 at Wadura, Sopore, Kashmir to evaluate the effect of bio-inoculants and inorganic fertilizers on the performance of strawberry (Fragariax ananassa Duch) under rainfed conditions. The treatments consisted of control (no culture), Azotobacter chroococcum, Azospirillum brasilense, Pseudomonas striata, Arbuscular mycorrhizal fungi, Azotobacter+Azospirillum, Azotobacter+Azospirillum+Pseudomonas striata, Azotobacter+Azospirillum+(Arbuscular mycorrhizal fungi) and recommended dose of fertilizers. The results indicated that application of recommended dose of fertilizers recorded significantly higher berry yield (6.02 tonne/ha), highest net returns (Rs 53 448/ha) and available nutrient (271.4 kg N and 18.62 kg P/ha) over rest of the treatments. Application of recommended dose of fertilizers increased available-soil N and P to the tune of 7.23, 8.38, 7.44 and 10.0% more over triple inoculation with Azotobacter+Azospirillum+Pseudomonas striata (253.1 N and 17.18 P kg/ha) and Azotobacter+Azospirillum+(Arbuscular mycorrhizal fungi) (252.6 N and 16.92 P kg/ha), respectively. Whereas multiinoculation of Azotobacter+Azospirillum+PSB and Azotobacter+Azospirillum+(Arbuscular mycorrhizal fungi) increased available soil N and P by 1.81, 16.9, 1.60 and 15.1% over their initial levels, respectively. Multi-inoculation of Azotobacter+ Azospirillum+PSB, being at par with Azotobacter+Azospirillum+Arbuscular mycorrhizal fungi recorded significantly higher viable count of Azotobacter chroococcum, Azospirillum brasilense and Pseudomonas striata over rest of the treatments. However, application of recommended dose of fertilizers significantly reduced the microbial population over control. Significant improvement in root infection (60.8%) and its spore density (271.6 spores/50 g soil) were observed with co-inoculation of Azotobacter+Azospirillum+Arbuscular mycorrhizal fungi over sole inoculation with arbuscular mycorrhizal fungi (53.5% and 222.7 spores/50 g soil). The maximum TSS (8.81°B), TSS/acidity ratio (12.77), total sugars (7.40%) and ascorbic acid (50.69 mg/100 g) were recorded under co-inoculation with Azotobacter+Azospirillum+Pseudomonus striata being at par with Azotobacter+Azospirillum+Arbuscular mycorrhizal fungi but significantly higher over application of recommended dose of fertilizers. However, maximum titratable acidity was recorded with control (0.82%) which was significantly higher over all the treatments.